2017
DOI: 10.5606/archrheumatol.2017.6129
|View full text |Cite
|
Sign up to set email alerts
|

Can Pentraxin-3 be a Candidate Marker in the Follow-Up of the Patients With Behçet’s Disease?

Abstract: Objectives: This study aims to assess the level of pentraxin-3 (PTX-3) as an inflammatory marker and compare it with C-reactive protein (CRP) levels in patients with Behçet's disease (BD). Patients and methods: Forty-two patients with BD (15 males, 27 females; mean age 39.7±8.6 years; range 20 to 64 years) and 42 age-and sex-matched healthy controls (14 males, 28 females; mean age 40.8±8.2 year; range 25 to 60 years) were included in the study. Serum CRP and plasma PTX-3 levels were measured. Subgroup analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The two most important characteristics of PTX3 are that it is locally produced in the endothelium and it reaches peak levels faster than CRP. [ 6 , 17 , 18 ] It is reported that PTX3 level is elevated in cardiovascular diseases and can be regarded as a biomarker of cardiovascular disease in the general population. [ 18 ] High serum PTX3 levels have also been associated with increased cardiovascular complications in conditions such as Cushing’s and Behçet’s diseases and in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two most important characteristics of PTX3 are that it is locally produced in the endothelium and it reaches peak levels faster than CRP. [ 6 , 17 , 18 ] It is reported that PTX3 level is elevated in cardiovascular diseases and can be regarded as a biomarker of cardiovascular disease in the general population. [ 18 ] High serum PTX3 levels have also been associated with increased cardiovascular complications in conditions such as Cushing’s and Behçet’s diseases and in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…It belongs to the same protein family as C-reactive protein (CRP); however, while CRP is mainly synthesized in the liver, PTX3 is mostly produced locally in the area of inflammation. 5,6 PTX3 has been associated with inflammation in cardiovascular diseases such as heart failure, atherosclerosis, acute coronary syndrome, peripheral vascular diseases, and rheumatic mitral valve stenosis. 4,[7][8][9] To our knowledge, there are no previous studies in the literature regarding serum PTX3 levels in ARF patients.…”
mentioning
confidence: 99%